What could make seaports more committed to air quality? A qualitative content analysis of key barriers, drivers, and enablers - Flóra Zsuzsanna Gulyás; Aseem Kinra (Journal of Shipping and Trade)
Abstract Background There is a growing need for seaports to find ways to reduce the air pollution they generate. A wide range of potential best practices exist, but what lies behind the decision to implement them? Prior studies have focused on either barriers, drivers, or enablers in this context. Thus, the purpose of this paper is to review existing research on various measures to reduce air pollution in seaports with the aspects of both barriers and enablers that influence the implementation of these actions. Methods To answer the research question, the authors conducted a systematic literature review using the databases of Web of Science (WoS) and Scopus. The initial search identified 247 studies in WoS and 589 studies in Scopus. After applying exclusion and inclusion criteria, a qualitative content analysis (QCA) was performed to narrow down the resulting articles and extract relevant information. The identified factors were then categorized, followed by a factor frequency analysis (FFA). Results Based on the final selection of 48 research articles, the review identified and categorized a total of 38 barriers and 28 enabling factors. The barriers were grouped into economic, technical, managerial, informational, and regulatory categories. The enabling factors were grouped into economic-financial, regulations and policies, informational, professional, and training categories. Aspects of finance and regulation are highlighted by the FFA. Findings Financial aspects play a crucial role on both the barriers and enablers side, while aspects such as information or professional training seem to be neglected. Barriers are diverse, while enablers focus mostly on regulations. With our findings, we contribute to previous work that will serve as a basis for further research on the interdependencies of influencing factors, as well as experts and stakeholders in developing suitable emission reduction (ER) strategies for citizens living and working in and around seaports. The ranking of importance as well as the degree of influence of the various factors depend on further aspects to be considered.